2009
DOI: 10.1093/applin/amp007
|View full text |Cite
|
Sign up to set email alerts
|

English Language Teachers' Conceptions of Research

Abstract: This article examines the conceptions of research held by 505 teachers of English from 13 countries around the world. Questionnaire responses supplemented by follow-up written and interview data were analyzed to understand teachers' views on what research is and how often they read and do it (and why or why not in each case). An understanding of these issues is central to the development of informed policies for promoting teacher research engagement, but relevant systematic evidence is lacking in the field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
314
1
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(390 citation statements)
references
References 23 publications
33
314
1
13
Order By: Relevance
“…In contrast, in the present study 40% of the 622 participants had between 20-30 years of experience. A small percentage of the participants did not hold any teaching degree, and that unlike the Borg (2009) study (see also Nassaji, 2012), only a small proportion held ma degrees.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast, in the present study 40% of the 622 participants had between 20-30 years of experience. A small percentage of the participants did not hold any teaching degree, and that unlike the Borg (2009) study (see also Nassaji, 2012), only a small proportion held ma degrees.…”
Section: Introductionmentioning
confidence: 86%
“…For example, Borg's (2009) study, the pillar of this investigation, was based on data collected from 505 teachers from 13 countries. A high proportion of respondents showed limited engagement in and with research due to a lack of time and, secondly, little knowledge about research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of research investigating the perceptions of L2 teachers about the relationship between SLA research and language pedagogy is less than the number of research advising teachers how to conduct it (Borg, 2009). To address this shortage existing between the relationship of SLA research and language pedagogy, one can stick to the dichotomy that made by Nassaji (2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In different studies, among them there were some international studies, Borg considered this issue. Borg (2009) examined the conception of research by 505 language teachers in 13 countries by using a questionnaire and a follow up interview. His study showed that "teachers held conceptions of research aligned with conventional scientific notions of inquiry" (p. 358).…”
Section: Literature Reviewmentioning
confidence: 99%